PROMOTING WILLINGNESS TO COMMUNICATE IN IMPROVING STUDENTS’ SECOND LANGUAGE ACQUISITION THROUGH LIVEWORKSHEETS.COM - Nissa Ilma Mukti; Rochmawati Rochmawati; Alfiah Nur Senta; Leo Candra Wahyu Utam; Zulvy Alivia Hanim (Journal of English for Academic and Specific Purposes, 2021)
This research investigates on the use of online platform media learning, namely liveworksheets.com to facilitate students’ willingness to communicate and acquire their second language in an online classroom. This study is considered essential to be taken account to, as it correlates to the current situation, in which classes are conducted online. To gain the data, questionnaire were distributed to third semester students who are learning English as part of their course for a foreign and second language in Universitas Islam Negeri Maulana Malik Ibrahim Malang. By applying a mixed-method research design, the result of the study presents that there were four main factors affecting students’ willingness to communicate when using liveworksheets.com. This includes learners’ behavioral intention, interlocutors, motivations and their affective-cognitive skills. Moreover, it was also noted that liveworksheets.com was found to be quite beneficial in facilitating students to acquire their second language through the mentioned aspects. Hopefully, the result of the study may bring new insight and contribute to the online teaching learning process that takes place nowadays both for teachers and second language learners.